Effectiveness of Chronic Disease Management Program in Improving “CERDIK” Healthy Behavior in Patients with Hypertension in Gunungkidul, Yogyakarta - Tri Puji Pangesti; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Hypertension is the single largest contributor to the global burden of disease (GBD). The Chronic Disease Management Program (Prolanis) is a health service system and a proactive approach implemented in an integrated manner. This study aimed to determine the effectiveness of Prolanis on the "CERDIK" healthy behavior for hypertensive patients.Subjects and Method: This cross-sectional study was conducted in hypertensive patients in 25 working areas of health centers in Gunungkidul, Special Region of Yogyakarta, from January to February 2020. A sample of 200 hypertensive patients was selected by simple random sampling. The dependent variable was the "CERDIK" healthy behavior for hypertensive patients. The independent variables were chronic disease management program (Prolanis), education level, peer support, family support, and sex. Other data were collected by using a questionnaire. Data were analyzed by path analysis using the Stata 13 application.Results: “CERDIK" healthy behavior for hypertensive patients increased with active prolanis activity (b= 5.00; 95% CI= 2.80 to 7.20; p <0.001), higher education (b= 1.52; 95% CI= 0.48 to 2.54; p= 0.004), strong family support (b= 1.38; 95% CI= 0.20 to 2.57; p= 0.023), strong peer support (b= 0.61; 95% CI= -0.67 to 2.51; p= 0.352), and female (b= 2.8; 95% CI= -5.01 to -0.64; p= 0.011). Education, family support, and peer support were associated with “CERDIK” healthy behavior through Prolanis.Conclusion: “CERDIK" healthy behavior for hypertensive patients increases with active prolanis activity, higher education, strong family support, strong peer support, and female. Education, family support, and peer support were associated with “CERDIK” healthy behavior through Prolanis.Keywords: Prolanis, “CERDIK” healthy behaviour, hypertension, path analysisCorrespondence: Tri Puji Pangesti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: tripujipangesti8@gmail.com. Mobile: 082312657779.Journal of Health Promotion and Behavior (2020), 05(03): 187-196https://doi.org/10.26911/thejhpb.2020.05.03.05.